Single-Stage Trans-Vestibular and Foley’s-Assisted Epispadias Repair (STAFER) for Girls with Incontinent Epispadias: A Retrospective Study from a Tertiary-Care Center - Minu Bajpai; Sachit Anand; Prabudh Goel (Uro, 2022)
Objective: The aim of this study was to evaluate the outcomes of single-stage trans-vestibular and Foley’s assisted epispadias repair (STAFER) technique in girls with incontinent epispadias. Methods: The records of all girls who had undergone epispadias repair and bladder neck plication via the STAFER technique over a four-year study period (January 2016 to December 2019) were retrospectively reviewed from the archives. A comparison of preoperative and postoperative functional outcomes was performed. Incontinence status was divided into four grades on the basis of severity: grade 0 (completely dry during day and night), grade 1 (occasional episodes of urine leakage leading to damp undergarments or requiring pads occasionally but not daily), grade 2 (frequent episodes of urine leakage with a dry period of <3 h), and grade 3 (completely incontinent). Renal bladder ultrasound (RBUS), micturating cystourethrogram (MCUG) scan, technetium-99m diethylenetriamine pentaacetate (DTPA) scan, and technetium-99m dimercaptosuccinic acid (DMSA) scan were performed to assess the upper tract function. Results: Nine girls with average (SD) age at surgery of 7.9 (3.8) years were operated on utilizing the STAFER technique during the study period. All cases had grade 3 incontinence and normal upper tracts prior to the surgery. Postoperatively, 8/9 girls had a dry period of more than 3 h. Six of them were completely dry and had no wetting episodes (grade 0 incontinence). DMSA and DTPA scans showed preserved upper tracts while MCUG scans revealed grade II VUR in only one case. Conclusions: In a limited cohort of girls with incontinent epispadias, the STAFER technique provides favorable functional outcomes in terms of continence and upper tract function. Further studies comprising a larger cohort of patients with a younger average age at surgery need to be conducted before definite conclusions regarding the efficacy of this technique are drawn.